2023
DOI: 10.3389/dyst.2023.11448
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinesia and dystonia

Abstract: Background: Bradykinesia has been reported in patients with dystonia. Despite this, the pathophysiological mechanisms of bradykinesia in dystonia remain largely unknown.Methods: We here performed a comprehensive literature search and reviewed clinical and experimental studies on bradykinesia in patients with dystonia.Results: Many studies have documented the presence of bradykinesia in patients with idiopathic and inherited isolated dystonia, regardless of the presence of parkinsonism. In addition, bradykinesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 151 publications
1
0
0
Order By: Relevance
“…In the present study, PTV decreased when moving with a given arm from the ipsilateral to the contralateral target, as it could be expected, due to the higher mechanical constraint affecting contralateral pointing movements. Consistently with previous investigations, its value was lower in CD patients with respect to normal participants, thus pointing to bradykinesia as a characteristic of this specific disorder ( Carboncini et al, 2004 ; Pelosin et al, 2009 ; Anastasopoulos et al, 2013 ; Nowak et al, 2013 ), in line with what it is generally observed for dystonic disturbances ( Paparella et al, 2023 ). This finding is consistent with the reduced agonist burst observed by Carboncini et al (2004) .…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, PTV decreased when moving with a given arm from the ipsilateral to the contralateral target, as it could be expected, due to the higher mechanical constraint affecting contralateral pointing movements. Consistently with previous investigations, its value was lower in CD patients with respect to normal participants, thus pointing to bradykinesia as a characteristic of this specific disorder ( Carboncini et al, 2004 ; Pelosin et al, 2009 ; Anastasopoulos et al, 2013 ; Nowak et al, 2013 ), in line with what it is generally observed for dystonic disturbances ( Paparella et al, 2023 ). This finding is consistent with the reduced agonist burst observed by Carboncini et al (2004) .…”
Section: Discussionsupporting
confidence: 90%
“…From a pathophysiological point of view, DT seems closer to nontremulous dystonia than ET ( Panyakaew et al, 2022 ). Based on a recent review article by Paparella et al, bradykinesia is frequently observed in dystonia involving basal ganglia, primary sensorimotor cortex and cerebellum in the pathological mechanism ( Paparella et al, 2023 ). Mild parkinsonian signs are an additional manifestation of dystonia arising mainly from the already mentioned basal ganglia dysfunction ( Haggstrom et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%